The course of the backward attacks in judo, after the first change of the rules, based on The World Championship from 2009 and 2011 in over 100 kg category. A pilot study - Pujszo, Małgorzata; Pujszo, Ryszard; Stępniak, Robert; Adam, Marek (Journal of Education, Health and Sport, 2016)
Pujszo Małgorzata, Pujszo Ryszard, Stępniak Robert, Adam Marek. The course of the backward attacks in judo, after the first change of the rules, based on The World Championship from 2009 and 2011 in over 100 kg category. A pilot study. Journal of Education, Health and Sport. 2016;6(6):223-234. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55180 http://ojs.ukw.edu.pl/index.php/johs/article/view/3566 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. The course of the backward attacks in judo, after the first change of the rules, based on The World Championship from 2009 and 2011 in over 100 kg category. A pilot study Pujszo Małgorzata1, Pujszo Ryszard2, Stępniak Robert3, Adam Marek4 1Students Science "WyKoNa" Kazimierz Wielki University, Bydgoszcz, Poland 2Centre for Education, Physical Education and Sport, Kazimierz Wielki University. Bydgoszcz, Poland 3Instituteof Physical Culture, Kazimierz Wielki University, Bydgoszcz, Poland 4Department of Combat Sports, University of Physical Education and Sport, Gdańsk, Poland Correspondence: Stępniak Robert Ph.D Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, ul. Sportowa 2, 85-091 Bydgoszcz, Polska email: <robi1969@wp.pl> Summary The aim of this article was to verify if the course, dynamics and time-structure of the judo fight in light of backwards attacks were changed after the radical change of the rules. It was presented the pilotage analyse of the fights containing the backward attack - based on the video recording from the World Championships in Rotterdam in 2009 (before the change of the rules) and The World Championships in Paris in 2011 (after the change of the rules) only in heaviest category The total of 97 male fights in over100 kgcategory were verified. The analysis of backward attacks conducted through the video recording of the fights from The World Championships in Rotterdam in 2009 (before the change of the rules) and The World Championships in Paris in 2011 after the first change of the rules showed identical frequency of backward attacks and identical number of fights terminated before the set time because of those attacks. However, the time structure of the fight showed the fight in a totally new picture. That, in turn, brings new challenges for the coaching staff and imposes the changes in defence tactics. Key words: judo, backward attack, World Championship.